Remediation of hexavalent chromium contaminated water through zero-valent iron nanoparticles and effects on tomato plant growth performance - Brasili, Elisa; Bavasso, Irene; Petruccelli, Valerio; Vilardi, Giorgio; Valletta, Alessio; Dal Bosco, Chiara; Gentili, Alessandra; Pasqua, Gabriella; Di Palma, Luca (Scientific reports, 2020)
Contaminated water with hexavalent chromium Cr(VI) is a serious environmental problem. This study aimed to evaluate the Cr(VI) removal by zero valent iron nanoparticles (nZVI) reduction process and the impact of Cr(VI), nZVI and combined treatment with nZVI and Cr(VI) on tomato growth performance. To evaluate the Cr(VI) toxic effect on germination capability, seeds were exposed to increasing Cr(VI) concentrations up to 1000 mg L −1 . The inhibition of seed germination and the decrease of hypocotyl and root length started from Cr(VI) 5 mg L −1 . Under treatment with Cr(VI) + nZVI 5 mg L −1 , seed germination, hypocotyl and root length resulted significantly higher compared to Cr(VI) 5 mg L −1 treatment. The impact of only nZVI was investigated on chlorophyll and carotenoid in leaves; iron levels in leaves, roots, fruits and soil; carotenoid, fat-soluble vitamin and nicotianamine in mature fruits. A significant increase of leaf chlorophyll and carotenoids was observed after nZVI 5 mg L −1 treatment compared to controls. No significant variations were observed in carotenoids, fat-soluble vitamins and nicotianamine levels after treatment with nZVI 5 mg L −1 in mature fruits. For their ability to reduce Cr(VI) and to stimulate tomato growth, nZVI might to be considered as alternative for remediation purposes.